The impact of the Iraq War 2003 on the British Society: A postcolonial study of Simon Stephens’s Motortown (2006) - Mousa, Ahmed Hasan; Sasani, Samira (Research Journal in Advanced Humanities, 2023)
This study explores the postcolonial impact of the 2003 Iraq war on British society, focusing on Simon Stephens's Motortown. The study addresses the contested field of postcolonialism, rejecting war while examining the transformation of culture and society resulting from colonialism. It explores nationalism, space and place, and the fusion of colonial and indigenous cultures. Concepts like hybridity, ambivalence, and the frame of war are explored within the postcolonial framework. Drawing on Homi K. Bhabha's influential work, The Location of Culture, the study examines the position of colonizer nations and their identity. Bhabha's concepts of cultural hybridity and colonial ambivalence illuminate the interactions between colonized nations and imperial colonizers, shaping the identities and cultures of both. Judith Butler's Frames of War: When Is Life Grievable? is incorporated, exploring how certain lives receive grief and political protection, while others remain invisible within social and political structures. By applying Butler's and Bhabha's concepts, the study analyzes the impact of the Iraq war on British society as depicted in Stephens's Motortown. This research contributes to understanding the cultural and social effects of the Iraq war on British society within a postcolonial framework and reveals the dynamics of power, hybridity, and ambivalence in the post-war context.